Acute Physiological Responses to Four Running Sessions Performed at Different Intensity Zones - Nuuttila, Olli-Pekka; Kyröläinen, Heikki; Häkkinen, Keijo; Nummela, Ari (International Journal of Sports Medicine, 2020)
This study investigated acute responses and post 24-h recovery to four running sessions performed at different intensity zones by supine heart rate variability, countermovement jump, and a submaximal running test. A total of 24 recreationally endurance-trained male subjects performed 90 min low-intensity (LIT), 30 min moderate-intensity (MOD), 6×3 min high-intensity interval (HIIT) and 10×30 s supramaximal-intensity interval (SMIT) exercises on a treadmill. Heart rate variability decreased acutely after all sessions, and the decrease was greater after MOD compared to LIT and SMIT (p<0.001; p<0.01) and HIIT compared to LIT (p<0.01). Countermovement jump decreased only after LIT (p<0.01) and SMIT (p<0.001), and the relative changes were different compared to MOD (p<0.01) and HIIT (p<0.001). Countermovement jump remained decreased at 24 h after SMIT (p<0.05). Heart rate during the submaximal running test rebounded below the baseline 24 h after all sessions (p<0.05), while the rating of perceived exertion during the running test remained elevated after HIIT (p<0.05) and SMIT (p<0.01). The current results highlight differences in the physiological demands of the running sessions, and distinct recovery patterns of the measured aspects of performance. Based on these results, assessments of performance and recovery from multiple perspectives may provide valuable information for endurance athletes, and help to improve the quality of training monitoring.
Keywords: endurance training; interval training; recovery; countermovement jump; heart rate variability; submaximal running test